Opiniones y hábitos de publicación en acceso abierto de los investigadores argentinos : Un estudio basado en los datos de la encuesta SOAP - Bongiovani, Paola (2012)
The aim of present work attempts was to discover the opinions and habits of Argentinean researchers regarding open access publishing in four research fields: Medicine, Physics and Astronomy, Agriculture and Biological Sciences and Social Sciences and Humanities. The study is based on the researchers' responses to the SOAP (Study of Open Access Publishing) survey conducted in 2010 and these results are compared with those revealed in the worldwide SOAP study as well as with the fi ndings of a previous study on the publication patterns of Argentina's scientifi c community. The conclusions and discussion caution that while open access publishing is considered beneficial, that consideration is not sufficient in itself for researchers to change their publication habits.